Maternal plasma and salivary anelloviruses in pregnancy and preterm birth - Kyathanahalli, Chandrashekara; Snedden, Madeline; Singh, Lavisha; Regalia, Camilla; Keenan-Devlin, Lauren; Borders, Ann E.; Hirsch, Emmet (Frontiers in Medicine, 2023)
Introduction: Human anelloviruses, including torque teno virus (TTV) and torque teno mini virus (TTMV), are ubiquitous in the general population and have no known pathogenicity. We investigated the prevalence and viral load of TTV and TTMV in plasma and saliva over pregnancy, and assessed their association with spontaneous or medically indicated preterm birth. Methods: This is a secondary analysis of the Measurement of Maternal Stress (MOMS) study, which recruited 744 individuals with singleton pregnancies from 4 US sites (Chicago, Pittsburgh, San Antonio, and rural Pennsylvania). Baseline outpatient visits took place in the second trimester (between 12’0 and 20’6/7 weeks’ gestation), and follow-up visits in the third trimester (between 32’0 and 35’6/7 weeks’ gestation). In a case-control study design, participants who delivered preterm (<37 weeks) resulting from spontaneous labor and/or preterm premature rupture of membranes (“sPTB”) were compared with participants experiencing medically indicated preterm birth (“iPTB”), or delivery at term (“controls”). Plasma and saliva samples obtained during the second and third trimesters were tested for the presence and quantity of TTV and TTMV using real-time PCR. Demographic data were obtained via self-report, and clinical data via medical record review by trained research personnel. Results: TTV was detected in plasma from 81% (second trimester) and 77% (third trimester) of participants, and in saliva from 64% and 60%. Corresponding detection rates for TTMV were 59% and 41% in plasma, and 35% and 24% in saliva. TTV and TTMV concentrations were similar between matched plasma and saliva samples. TTV prevalence and concentrations were not significantly different between groups (sPTB, iPTB, and controls). However, plasma TTMV in the third trimester was associated with sPTB and earlier gestational age at delivery. The iPTB group was not different from either the sPTB or the control group. In saliva, concentrations of TTV and TTMV were similar among the three groups. Both TTV and TTMV were more prevalent with increasing parity and were more common in Black and Hispanic participants compared to non-Hispanic White participants. Conclusions: Anellovirus presence (specifically, TTMV) in the third trimester may be associated with preterm birth. Whether this association is causative remains to be determined.